Peningkatan Kemampuan Penalaran Matematik Dan Kemandirian Belajar Siswa SMP Melalui Pendekatan Problem Solving - Yova Chintiya; Eka Senjayawati; Asep Ikin Sugandi (Journal on Education, 2019)
The aim of this study is for examine the learning independence of junior high school students whose learning use problem solving approach compared by scientific approach. Increased mathematical reasoning abilities of students who learn using the problem solving approach compared by scientific approach. The method used in this study lis quasi-experimental by taking two classes not randomly, in the first class get learned by using problem solving approach and the second class get learned by using scientific approach. The population is students in Bandung City with a sample that took two classes of VII which consisted of experimental class and the control class. The instrument used is reasoning abilities question on triangle and quadrilaterals problem and students learning independence questionnaires by using a Likert scale to see students’ learning independence toward problem solving approaches. The data prossesed in this study are pretest, posttest and n-gain scores using the help of Microsoft Office Excel 2010 and IBM SPSS Statistic 24. The result obtained are mathematical reasoning abilities and learning independence of junior high school students whose learning uses problem solving approaches better than those who using scientific approach, an increase in mathematical reasoning ability is better than one that uses scientific approach.